2016
DOI: 10.7554/elife.19042.022
|View full text |Cite
|
Sign up to set email alerts
|

Author response: Defining key roles for auxiliary proteins in an ABC transporter that maintains bacterial outer membrane lipid asymmetry

Abstract: In Gram-negative bacteria, lipid asymmetry is critical for the function of the outer membrane (OM) as a selective permeability barrier, but how it is established and maintained is poorly understood. Here, we characterize a non-canonical ATP-binding cassette (ABC) transporter in Escherichia coli that provides energy for maintaining OM lipid asymmetry via the transport of aberrantly localized phospholipids (PLs) from the OM to the inner membrane (IM). We establish that the transporter comprises canonical compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Low-resolution cryo-EM maps of the MlaBDEF core complex, from Escherichia coli (MlaBDEFec) (2) and Acinetobacter baumannii (MlaBDEFab) (7) have also been reported, and revealed the overall architecture of the complex, but did not allow to elucidate the molecular details of lipid binding and transport. Opinions about the directionality of lipid transport by the MLA system have been highly controversial, with initial reports suggesting that it recycles lipids from the OM to the IM (2,8,9), but recent results (7,10,11) indicated that it might exports glycerophospholipids to the outer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Low-resolution cryo-EM maps of the MlaBDEF core complex, from Escherichia coli (MlaBDEFec) (2) and Acinetobacter baumannii (MlaBDEFab) (7) have also been reported, and revealed the overall architecture of the complex, but did not allow to elucidate the molecular details of lipid binding and transport. Opinions about the directionality of lipid transport by the MLA system have been highly controversial, with initial reports suggesting that it recycles lipids from the OM to the IM (2,8,9), but recent results (7,10,11) indicated that it might exports glycerophospholipids to the outer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Key components, including LPS, integral β-barrel proteins, and lipoproteins, are transported and assembled unidirectionally into the OM by the Lpt (Okuda et al, 2016), Bam (Hagan et al, 2011), and Lol machinery (Okuda & Tokuda, 2011), respectively. Recently, several systems, including the OmpC-Mla system and the Tol-Pal complex, have been implicated in PL transport between the IM and the OM (Shrivastava et al, 2017;Ekiert et al, 2017;Ercan et al, 2018;Thong et al, 2016;Hughes et al, 2019). However, much of bulk PL transport between the two membranes, which occurs in both directions (Donohue-Rolfe & Schaechter, 1980;Jones & Osborn, 1977;Langley et al, 1982), is still largely unknown (Shrivastava & Chng, 2019).…”
Section: Introductionmentioning
confidence: 99%